Pharmacogenetic landscape of DPYD variants in south Asian populations by integration of genome-scale data. (February 2018) - Hariprakash, Judith M; Vellarikkal, Shamsudheen K; Keechilat, Pavithran; Verma, Ankit; Jayarajan, Rijith; Dixit, Vishal; Ravi, Rowmika; Senthivel, Vigneshwar; Kumar, Anoop; Sehgal, Paras; , Aradhana; Sonakar, Akhilesh K; et al.
Aim: Adverse drug reactions to 5-Fluorouracil(5-FU) is frequent and largely attributable to genetic variations in the DPYD gene, a rate limiting enzyme that clears 5-FU. The study aims at understanding the pharmacogenetic landscape of DPYD variants in south Asian populations.Materials & methods: Systematic analysis of population scale genome wide datasets of over 3000 south Asians was performed. Independent evaluation was performed in a small cohort of patients.Results: Our analysis revealed significant differences in the the allelic distribution of variants in different ethnicities.Conclusions: This is the first and largest genetic map the DPYD variants associated with adverse drug reaction to 5-FU in south Asian population. Our study highlights ethnic differences in allelic frequencies.